Optimization and performance comparison for galloping-based piezoelectric energy harvesters with alternating-current and direct-current interface circuits. (14th June 2017) - Tan, Ting; Yan, Zhimiao; Lei, Hong
Abstract: Galloping-based piezoelectric energy harvesters scavenge small-scale wind energy and convert it into electrical energy. For piezoelectric energy harvesting with the same vibrational source (galloping) but different (alternating-current (AC) and direct-current (DC)) interfaces, general analytical solutions of the electromechanical coupled distributed parameter model are proposed. Galloping is theoretically proven to appear when the linear aerodynamic negative damping overcomes the electrical damping and mechanical damping. The harvested power is demonstrated as being done by the electrical damping force. Via tuning the load resistance to its optimal value for optimal or maximal electrical damping, the harvested power of the given structure with the AC/DC interface is maximized. The optimal load resistances and the corresponding performances of such two systems are compared. The optimal electrical damping are the same but with different optimal load resistances for the systems with the AC and DC interfaces. At small wind speeds where the optimal electrical damping can be realized by only tuning the load resistance, the performances of such two energy harvesting systems, including the minimal onset speeds to galloping, maximal harvested powers and corresponding tip displacements are almost the same. Smaller maximal electrical damping with larger optimal load resistance is found for the harvester with the DC interface when compared to those for the harvester with the AC interface. At large wind speeds when the maximal electrical damping rather than the optimal electrical damping can be reached by tuning the load resistance alone, the harvester with the AC interface circuit is recommended for a higher maximal harvested power with a smaller tip displacement. This study provides a method using the general electrical damping to connect and compare the performances of piezoelectric energy harvesters with same excitation source but different interfaces.